PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BABADAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , ESA ANGGER WINASIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In the mapping work mainly to produce large-scale maps it is necessary to design appropriate measures and methods in order to produce a good map and according to specifications recommended. In the event contains an error then definite measurement in order to avoid or minimize such errors must be corrected. The first mapping stage is to develop Horizontal Control Framework which included surveys and planning orientation, the horizontal angle measurements, the distance between the point of the polygon, and the measurement of binding azhimut. Measurements of Vertical Control Framework includes measurement height difference between point of polygon and the distance between the polygon slag. Measurement of both situations detailed planimetric detail and high detail. Data processing of Horizontal Control Framework assigned the coordinates of polygon point, count the height difference by using the form to calculate the high-count polygon point. The Cartographic is done digitally by using Surpac software and ArcGIS. The map checking is done by taking multiple samples for testing in the field in order to determine the quality and accuracy of the resulting map. Results of measurement and map checking are match by a specifications. Next the results of spatial information is presented by a map of the situation with scale of 1: 500 in the Babadan Babadant, Desa Beluk, Kecamatan Bayat, Kabupaten Klaten, Central Java Province.